Consideration of Antenna Pattern by Elevation in Recommendation ITU-R P. 2001 - Chernov, A.; Kovshar, V.; Kaliuzhnyi, M.; Zheng Yu (IEEE, 2020)
The question of the practical application of the comprehensive universal Recommendation ITU-R P.2001 in calculating the electromagnetic compatibility of electronic systems is considered. In this Recommendation antenna patterns are assumed isotropic in elevation plane. It is shown that to increase an accuracy of calculations by this technique, it is necessary to take into account the difference between the terminal antennas pattern and isotropic antennas. A detailed analysis of the propagation of radio waves sub-model for reflection from the sporadic layer E. The significant influence of the distance between the terminals and the types of their antennas on the calculation results for this sub-model. The quantitative corrections for typical short-wave and ultra-short wave antennas are determined. The directions of further research were selected to increase the accuracy of calculations of the propagation of radio waves when using the Recommendation ITU-R P.2001.
Keywords: sporadic-E reflection; antenna pattern; prorogation radio wave; electromagnetic compatibility